Clinical pharmacology considerations in biologics development - Zhao Liang; Ren Tian-hua; Wang Diane D (Acta Pharmacologica Sinica, 2016)
Biologics, including monoclonal antibodies (mAbs) and other therapeutic proteins such as cytokines and growth hormones, have unique characteristics compared to small molecules. This paper starts from an overview of the pharmacokinetics (PK) of biologics from a mechanistic perspective, the determination of a starting dose for first-in-human (FIH) studies, and dosing regimen optimisation for phase II/III clinical trials. Subsequently, typical clinical pharmacology issues along the corresponding pathways for biologics development are summarised, including drug-drug interactions, QTc prolongation, immunogenicity, and studies in specific populations. The relationships between the molecular structure of biologics, their pharmacokinetic and pharmacodynamic characteristics, and the corresponding clinical pharmacology strategies are summarised and depicted in a schematic diagram.